60-minute estate planner : - Kraemer, Sandy F. (AMACOM, American Management Association, 2006)
The book clarifies all the different possible elements of an estate plan, including IRAs, living trusts, life insurance, annuities... It shows how to communicate with heirs; Manage medical decisions and provide for the special needs of young and old; Reduce, defer, and eliminate as much gift, estate, inheritance, and other tax as possible; Use estate planning professionals and save on professional fees for planning and administration.